2018
DOI: 10.3389/fphys.2018.01752
|View full text |Cite
|
Sign up to set email alerts
|

Linking Arrhythmias and Adipocytes: Insights, Mechanisms, and Future Directions

Abstract: Obesity and atrial fibrillation have risen to epidemic levels worldwide and may continue to grow over the next decades. Emerging evidence suggests that obesity promotes atrial and ventricular arrhythmias. This has led to trials employing various strategies with the ultimate goal of decreasing the atrial arrhythmic burden in obese patients. The effectiveness of these interventions remains to be determined. Obesity is defined by the expansion of adipose mass, making adipocytes a prime candidate to mediate the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 118 publications
(149 reference statements)
2
36
0
1
Order By: Relevance
“…Whether such age-dependent changes rely on autophagy modulation in dermal progenitors as described here for subcutaneous fat has not been investigated, but autophagic decline is a well-known feature in ageing. Also, related to TGF-BMP pathway, obesity can promote heart arrhythmias through fibrosis accumulation [31], and TGFb is up regulated in the atria of rats fed a HFD which favors fibrosis [32].…”
Section: Atg7 Deficiency In Progenitors Favors Subcutaneous Fat Beigementioning
confidence: 99%
“…Whether such age-dependent changes rely on autophagy modulation in dermal progenitors as described here for subcutaneous fat has not been investigated, but autophagic decline is a well-known feature in ageing. Also, related to TGF-BMP pathway, obesity can promote heart arrhythmias through fibrosis accumulation [31], and TGFb is up regulated in the atria of rats fed a HFD which favors fibrosis [32].…”
Section: Atg7 Deficiency In Progenitors Favors Subcutaneous Fat Beigementioning
confidence: 99%
“…Mazurek et al investigated human epicardial adipose tissue and found that epicardial adipose tissue was a source of several cytokines, including monocyte chemotactic protein 1, interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α, all of which may promote the genesis of atherosclerosis [7]. The adipocytokines and metabolites of pericardial fat also could result in mitochondrial dysfunction, autonomic nervous dysfunction, and cardiomyocyte death, all of which might lead to heart failure [8]. Our previous study also demonstrated that adipocytokines from pericardial fat could affect the ion currents of cardiomyocytes, which might contribute to the mechanisms of arrhythmogenesis [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, increased leptin levels can lead to increased aldosterone secretion, endothelial dysfunction, increased vascular stiffness, hypertension, and cardiac hypertrophy, all of which could contribute for AF pathogenesis 22 . Moreover, adipokines and metabolites from EAT are associated with systemic inflammation, oxidative stress, and autonomic dysfunction, resulting in a pro‐arrhythmogenic state 14 …”
Section: Discussionmentioning
confidence: 99%
“…The local effect involves adipocyte infiltration into the atrial myocardium 9,10 and fibrosis of the neighboring atrial tissue by paracrine secretion of profibrotic adipokines 11‐13 . The remote effect, on the other hand, arises from the systemic secretion of adipokines and metabolites 14 . Furthermore, ganglionated plexuses are located in EAT, altering the electrophysiological properties of atrial remote areas 15,16 .…”
Section: Introductionmentioning
confidence: 99%